Diode endovascular laser treatment in venous malformations of the upper aerodigestive tract. Issue 5 (May 2016) - Simon, François; Le Clerc, Nicolas; Salvan, Didier; Sauvaget, Elisabeth; Faucon, Benoît; Borsik, Michel; Herman, Philippe; Bisdorff, Annouk
Abstract: Purpose: Venous malformations of the upper aerodigestive tract can cause pain, dysphagia, obstructive sleep apnea, and rarely bleeding. We studied 980-nm diode endovenous laser therapy. Material and methods: This is a 2007–2014 retrospective study in our vascular anomalies center. Data on patients' clinical history, polysomnography, magnetic resonance imaging, and treatment were collected. Patients were contacted for Epworth Sleepiness Scale and Eating Assessment Tool (EAT-10) scores to evaluate sleepiness and dysphagia before and after laser therapy. Results: We included 32 patients (mean age 41 years) presenting with obstructive sleep apnea (n = 18) and dysphagia (n = 13). With a mean follow-up of 39 months, average Epworth Sleepiness Scale score fell from 17.3 to 10.4 (p = 0.015), EAT-10 score from 8.2 to 3.5 (p = 0.002) and apnea–hypopnea index from 47.5 to 24.7 (p = 0.01). Of the sleep apnea patients, 89% required continuous positive airway pressure before and 50% afterward (p = 0.016). Conclusions: Diode endovascular laser treatment seems to be a safe and effective treatment option in venous malformations of the upper airways.